Irrigation Scheduling for Tropical Fruit Groves in South Florida - Kati W. Migliaccio; Yuncong C. Li (EDIS)
Irrigation scheduling can be accomplished using different tools, each with its benefits and weaknesses. It is critical to use each tool as it is intended to ensure tropical fruit trees have the irrigation water they need. This revised 6-page fact sheet was written by K. W. Migliaccio and Y. C. Li, and published by the UF Department of Agricultural and Biological Engineering, February 2012.